Construction of Scale to Measure the Attitude of the Scientists towards Organizational Climate - Mohmmad Yunus , C. P. Desai and I. M. Khan, (Indian Journal of Extension Education, 2017)
Ascale was developed to measure the scientists' attitude towards organizational climate based on “Scale Product Method”which combines the Thurston's technique of Equal Appearing Interval Scale for selection of the items and Likert'stechniques of summated rating for ascertaining the response on the scale. A tentative list of 79 statements was draftedkeeping in view the applicability of statements to the area of study. The statements collected were edited in the light of thecriteria suggested by Edward. These statements were framed in such a way that they expresses feelings of the scientiststowards organizational climate. The score of each individual item on the scale was calculated by summing up the weightsof the individual items. In all, 29 statements were selected as they were found to be non-ambiguous and non factual. Scaleand Q value of each statement was calculated by using Thurstone and Chave inter-quartile range. Finally, the scaleconsisted of 12 statements whose median (scale) values were greater than Q values. However, when a few statements hadthe same scale values, statements having lowest Q value were selected by arranging the scale value in an order. Reliabilitywas tested with 20 respondents and its value was 0.72 and validity of the scale was examined.